Educação cooperativista e mecanismos de comunicação organizacional nas cooperativas do estado do Goiás. - Silva, Maira Sousa (Universidade Federal do Tocantins, 2023)
This research aims to verify the way cooperative education and organizational communication mechanisms occur in state cooperatives. This is an exploratory and descriptive study that methodologically follows quantitative and qualitative criteria for analyzing the obtained data. In a first moment, a systematic review of the literature on cooperative education in the last five years in Brazil was carried out, and subsequently, a survey with the application of an online questionnaire in cooperatives in Goiás, which presented a return of 9.92 %, this being the representative number of the analyzed sample. The collected data were analyzed by SPSS and showed how these social organizations perform and conceive the work of this education model, as well as organizational communication presents challenges to better develop the cooperative scenario in Goiás.